Who gets the Credit? Determinants of the Probability of Default in the German Hospital Sector - Boris Augurzky; Dirk Engel; Christoph Schwierz (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2006)
Huge underinvestment increases the need for private borrowing in the German hospital sector, the access to which is partly determined by the probability of default (PD) of individual hospitals. Using ordinary least squares and quantile regression techniques this paper provides first empirical evidence of its kind to evaluate the PD in the hospital sector and its constituent determinants. Based on annual account and medical data from 17% of all German hospitals we find that the current average probability of default amounts to approximately 1.7%, which is slightly higher than the average probability for all German firms. Among other determinants, we find that public ownership significantly increases the risk of default, while private for-profit and private not-for-profit hospitals do not differ. Moreover, demographic change in the form of population growth is confirmed to be relevant for the PD.
Keywords: I11; L31; 330; Hospital profitability; quantile regression; probability of default; ownership type theories